Mengembangkan Pemahaman Matematis Siswa Madrasah Ibtidaiyah Melalui Lembar Kegiatan Siswa Berbasis Kearifan Lokal - Carlian, Yayan; Pratiwi, Inne Marthyane (JMIE (Journal of Madrasah Ibtidaiyah Education), 2018)
Mathematical understanding is a process that is mastered and studied by Madrasah Ibtidaiyah students in the process of mathematics learning. The process is improved through various activities in the classroom. Therefore, teachers need to facilitate the improvement of students' mathematical understanding. One of the ways to facilitate the improvement of students' mathematical understanding is through the use of students’ activities worksheet based on local wisdom. It is a teaching material that contains mathematical tasks that incorporate cultural values. With the integration of the local wisdom, students will be aware of the noble cultural values of the region and increase the love of students to the culture. The result of the development of students’ activities worksheet based on local wisdom is to make students have a good ability in mathematical understanding and cultural principles of life.